TEACHING PRACTICUM OF ENGLISH SUBJECT: PERCEPTION ON STUDENT TEACHER' PERFORMANCE IN TWO JUNIOR HIGH SCHOOL IN BANDUNG - Martina Herawatiningsih, - (2011)
The study entitled The Teaching Practicum of English Subject: Perception on Student Teachers' Performance in Two Junior High Schools in Bandung aims at revealing how student teachers' performance is perceived and unveiling problems encountered during teaching practicum. The current study employed descriptive method. The study was conducted among 140 students, five student teachers, three cooperating teachers and two university supervisors. The data were collected by means of questionnaires, classroom observation and interview. The obtained data were further analyzed based on the framework from Schwebel et al. (1996). Findings confirm that student teachers' performance is perceivedsimilarly by the respondents. All respondents give positive response toward student teachers' performance. In students' view, student teachers show good performance in the course of teaching practicum. Their good performance is denoted by student teachers' great concern on promoting students' participation. From the perspective of student teachers, they perceive themselves as having good performance. Putting great concern on giving homework and eliciting feedback signify their good performance. Of cooperating teachers, they consider student teachers' performance very good. Their excellentperformance is indicated by the high frequency of occurrence on eliciting learning objective, citing comprehensible examples and giving homework. As for university supervisors, theyperceive that the student teachers have good performance. Their good performance is portrayed by their great emphasis on keeping interacting with students and controlling students' group work. Concerning student teachers' problems, three major problems are identified, namely disorganized classroom, difficulty in designing accommodative classroom activities and difficulty in varying activities and using multiple levels of Bloom's. To conclude, student teachers' performance has not been free-drawback. There are three pedagogical aspects that requirefurther improvement. Among these aspects, students' differences accommodation calls for the biggest improvement. Based on the findings, it is recommended that teacher education institutionsprovide student teachers with intact knowledge about pedagogical principles for their teaching. Besides, all parties involved in teaching practicum program should propose strategies for accommodating the weaknesses of student teachers' performance.